Ethnocultural Elements in Indirect Translation: From Vovchok’s Ukrainian Folk Stories to Cadot’s French via Turgenev’s Mediating Text - Diachuk, Liudmyla (Verbum, 2026)
This article examines the reproduction of culturally marked elements, including realia, phraseological expressions, and diminutive suffixes, in the indirect translation of Marko Vovchok’s Folk Stories from Ukrainian into French via Ivan Turgenev’s Russian translation. The aim of the study is to assess how the use of an intermediary language affects the rendering of cultural and stylistic aspects of the source text. The data were collected through the excerption of culture-specific units and analysed using comparative and contrastive methods. The findings show that the mediating text influences the conveyance of cultural elements in the target translation. Turgenev’s translation partially neutralises ethnocultural realia, reduces emotional expressiveness, and simplifies the folk-colloquial tone. Cadot’s French translation, based on a Russian intermediary, conveys these concepts through transliteration with explication, cultural equivalents, and descriptive adaptation, sometimes compensating for losses to ensure intelligibility for the target audience. Overall, these changes can be classified as preservation, partial adaptation, loss/neutralisation, or amplification/explanation. The analysis reveals that the translation outcomes ultimately depend on the translator’s creativity and cultural awareness. Further research on indirect translation could provide deeper insights into the reception of Ukrainian literature within the French-speaking cultural space.